Temperature Characteristics and Junction Temperature Estimation Methods for SiC MOSFET and Si IGBT - NING Puqi; LI Lei; WEN Xuhui; ZHANG Dong (Kongzhi Yu Xinxi Jishu)
The output characteristic test circuit, leakage current test circuit and double pulse test circuit were set up to study the effect of temperature characteristics of 1 200 V SiC MOSFET and 1 200 V Si IGBT on output characteristic, leakage current, switch characteristic and the loss. Based on the variable performances, different junction temperature estimations were proposed. The estimation indicated that the on-state voltage and leakage current of SiC MOSFET and Si IGBT would increase with the junction temperature rising. The same applied to turn-on loss and turn-off loss of Si IGBT. Meanwhile, turn-on loss of SiC MOSFET would increase at first and then decrease, but turn-off loss would increase with junction temperature rising. Switching time of Si IGBT varied monotonously, but no obvious regularity existed in switching time of SiC MOSFET.